Influence of Filler Precoating and Printing Parameter on Mechanical Properties of 3D Printed Acrylonitrile Butadiene Styrene/Zinc Oxide Composite. Issue 1 (2nd January 2019) - Aw, Yah Yun; Yeoh, Cheow Keat; Idris, Muhammad Asri; Teh, Pei Leng; Elyne, Wan Nurshaznie; Hamzah, Khairul Amali; Sazali, Shulizawati Aqzna
ABSTRACT: Acrylonitrile butadiene styrene (ABS)/zinc oxide(ZnO) composites have been fabricated via fused deposition modelling technique. The effect of filler precoating and printing parameters on mechanical properties of the composites are investigated. The incorporation of precoated fillers and increase of infill density improve the tensile strength, Young's modulus and hardness of the composites. Printing pattern determines mainly the tensile properties of the composites but has no significant effect on the hardness. Based on experimental results, it is suggested that line pattern printed with precoated fillers at medium dispenser speed and 100% infill density has resulted improved mechanical properties. GRAPHICAL ABSTRACT: